Comparison of LMA Protector vs. endotracheal tube in patients undergoing laparoscopic surgery: a randomised controlled trial - SARAÇOĞLU, AYTEN (My University, 2022)
© 2022 Via Medica. All rights reserved.Background: Recent advances in airway management have led to supraglottic airway devices (SAD) being increasingly often chosen instead of tracheal intubation for laparoscopic surgery. However, there are ongoing arguments regarding the use of SAD due to worries about the risks of insufficient ventilation and pulmonary aspiration. The LMA Protector is a second generation SAD which was put into use recently. This prospective randomised trial investigated whether the LMA Protector was comparable to the tracheal tube regarding respiratory parameters, perioperative complications and haemodynamic parameters in patients undergoing laparoscopic surgery. Methods: A total of 154 adult patients were randomised to two groups: Group 1 (tracheal intubation) and Group 2 (LMA Protector). Achieving adequate depth of anaesthesia, the patients were either intubated or the LMA Protector was placed. The initial baseline measurements were recorded including tidal volume, peak inspiratory pressure (PIP), oropharyngeal leak pressure (OLP) and haemodynamic parameters. These measurements were repeated and recorded again following pneumoperitoneum and recovery from anaesthesia. Results: At the mean age of 52.22 ± 13.90 years 77 patients were intubated and in 77 patients the LMA Protector was applied. Following insertion of the airway device and pneumoperitoneum, the heart rate was higher in the intubation group. In the LMA Protector group OLP measures were found to be statistically similar. The mean Brimacombe fibreoptic visualisation score was 2.12 ± 0.58 and the rate of requirement of optimisation was 15% in the LMA Protector group. Conclusions: With high OLP, better haemodynamic parameters and low laryngeal view scores, we concluded that the LMA Protector can be used safely in patients undergoing laparoscopic surgery.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; anaesthesia; intubation; laparoscopic surgery; LMA protector: laparoscopic surgery; anaesthesia; intubation; LMA protector.